A composite collector for floating lead-zinc sulfide ore, a preparation method, application and a matching intelligent emulsification dosing system thereof
Patent Information
- Application Number
- CN202611073211.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-20
- Publication Date
- 2026-10-16
AI Technical Summary
[0006]基于上述技术问题,本发明摒弃传统单剂筛选与简单复配的设计思路,基于硫化铅锌矿两段浮选的界面作用差异,从分子设计与界面化学参数调控出发,通过铜铅、锌分选专用复合捕收剂的定向组分配伍,同步实现HLB、CMC与浊点的精准调控,匹配低碱无石灰浮选工艺,并配套多级乳化智能加药装备,解决传统药剂选择性与捕收力难以兼顾、高碱工艺弊端多、低温适应性差、环保性能不足、药剂利用率低的一系列问题
1、两段专用复合捕收剂的协同设计,无需添加石灰即可实现高硫矿石的铅锌高效分离,打破了高硫矿必须高碱分选的技术偏见;铅、锌回收率均突破90%,锌精矿铁含量降至11%以下,伴生银回收率较传统高碱工艺提升10个百分点以上。
Smart Images

Figure CN122913002A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of sulfide ore flotation technology in mineral processing engineering, specifically to a composite collector for the flotation of sulfide lead-zinc ore, its preparation method, application, and supporting intelligent emulsification dosing system. Background Technology
[0002] Flotation of lead-zinc sulfide ores is a core process for beneficiation of non-ferrous metals in my country. Currently, industrial production generally relies on high-alkali lime processes and traditional xanthate / black reagent systems, which have problems such as low recovery rate of associated silver, severe pipe scaling, difficulty in tailings settling, and poor environmental performance of some reagents. At the same time, in cold regions, the low temperature of the slurry in winter leads to poor reagent dispersion and large fluctuations in separation indicators, which have become common problems in the industry.
[0003] In the prior art, Chinese patent CN115672561B discloses a zinc flotation collector for lead-zinc sulfide ore and its preparation method. It uses a system of dialkyl dithiocarbamate compounded with hydrocarbon dithiophosphate thioether ester, 2-octanol, and diesel oil, which improves the zinc flotation recovery rate to some extent, but still has significant drawbacks: First, the reagent is designed only for the zinc flotation stage, without a dedicated reagent for the copper-lead mixed flotation stage, making it impossible to form a synergistic integrated separation system between the two stages. The lead stage still requires a highly alkaline environment due to insufficient selectivity. Second, it is only a simple physical compound of components, without targeted control from the perspectives of interfacial chemistry such as hydrophilic-lipophilic balance, critical micelle concentration, and cloud point. The reagent is prone to precipitation at low temperatures, exhibits poor micelle stability, and its performance fluctuates greatly in cold winters in high-altitude mining areas. Third, it lacks a dedicated preparation process and dosing equipment, leading to easy stratification of the reagent during storage and low on-site utilization.
[0004] Other studies have disclosed the synthesis process of sulfur and nitrogen collectors and multi-stage emulsification dosing systems, but these are mostly applied to copper ore flotation or coal beneficiation, and have not been specifically adapted for the characteristics of reagents used in the two-stage separation of lead-zinc sulfide ores, making it impossible to directly apply them to solve the aforementioned technical problems. Furthermore, some existing reagents contain benzene ring structures, resulting in low biodegradability and failing to meet the current environmental protection requirements of green mines.
[0005] To address the shortcomings of existing technologies, there is an urgent need to develop a two-stage synergistic, low-temperature stable, low-alkali environmentally friendly, reagent and equipment integrated composite collector system for the flotation of lead-zinc sulfide ores, so as to achieve efficient and green separation of high-altitude and high-sulfur ores. Summary of the Invention
[0006] Based on the aforementioned technical problems, this invention abandons the traditional design approach of single-agent screening and simple compounding. Based on the difference in interfacial interaction between the two stages of flotation of sulfide lead-zinc ore, it starts from molecular design and interfacial chemical parameter control. Through the directional combination of special composite collectors for copper-lead and zinc separation, it simultaneously achieves precise control of HLB, CMC and cloud point, matches the low-alkali lime-free flotation process, and is equipped with multi-stage emulsification intelligent dosing equipment. This solves a series of problems such as the difficulty in balancing selectivity and collecting power of traditional reagents, the many drawbacks of high-alkali processes, poor low-temperature adaptability, insufficient environmental performance, and low reagent utilization.
[0007] In a first aspect, this invention protects a composite collector for the flotation of lead-zinc sulfide ores, the composite collector being composed of a copper-lead mixed flotation collector HX-01 and a zinc flotation collector HX-02; the composite collector is free of benzene ring structures and has a biodegradability rate of ≥75% after 48 hours; the copper-lead mixed flotation collector HX-01 comprises the following components by weight: 60-80 parts of dialkyl dithiophosphate, 15-30 parts of thiocyanate, and 3-12 parts of non-polar hydrocarbon oil; the collector H... X-01 has a hydrophilic-lipophilic balance (HLB) of 7.5~9.0, a critical micelle concentration (CMC) ≤32mg / L, and a cloud point ≥14℃; the zinc flotation collector HX-02 comprises the following components by weight: 65~90 parts of thiocyanate, 2~8 parts of hydroxy fatty alcohol, and 4~15 parts of nonpolar hydrocarbon oil; the zinc flotation collector HX-02 has a hydrophilic-lipophilic balance (HLB) of 8.0~9.5, a critical micelle concentration (CMC) ≤28mg / L, and a cloud point ≥15℃.
[0008] Furthermore, in the copper-lead mixed flotation collector HX-01, the dialkyl dithiophosphate is butylammonium black powder, and the thiocyanate is diethylaminodithiocarbamate alkyl ester; in the zinc flotation collector HX-02, the thiocyanate is N,N-diethyldithiocarbamate cyanoethyl ester, and the hydroxy fatty alcohol is 2-octanol.
[0009] 1. Molecular structure selection and design principles Based on the differences in interfacial interactions between the two stages of flotation of lead-zinc sulfide ores, this study selects, combines, and functionalizes existing commercial collector molecules from three dimensions: molecular structure, mineral adsorption compatibility, interfacial performance, and environmental attributes. Through molecular-level functional complementarity, it achieves interfacial effects that cannot be achieved by traditional single agents or simple compounding.
[0010] (1) Copper-lead mixed flotation collector HX-01 The primary collector used is butylammonium black powder, with dithiophosphate at the polar end of the molecule, which is used to collect Pb in the galena lattice. 2+It exhibits high chelation selectivity, with weak adsorption forces on sphalerite and pyrite, ensuring effective lead-zinc separation under low-alkali conditions at the molecular level. The hydrophobic end is a symmetrical butyl carbon chain with moderate length, allowing for controllable hydrophobicity and preventing excessive collection of gangue and iron sulfide minerals. The auxiliary collector is diethylaminodithiocarbamate alkyl ester (thionitrogen ester), with a dithiocarbamate anion at its polar end, resulting in higher coordination atom density. This allows it to adsorb onto high-energy sites such as lattice defects and step positions in fine-grained galena, compensating for the insufficient collecting power of butylammonium black reagent for fine-grained lead minerals. The hydrophobic end is a short-chain ethyl group, ensuring no significant sacrifice in overall system selectivity. The functional additive is a non-polar hydrocarbon oil (kerosene or 0# diesel), a pure non-polar alkane molecule that can insert into the hydrophobic core of the collector micelles, enhancing the thickness of the hydrophobic film after adsorption on the mineral surface. Simultaneously, it shields the collector from indiscriminate adsorption by ore slime, reducing ineffective reagent consumption.
[0011] (2) Zinc flotation collector HX-02 The primary collector is N,N-diethyldithiocarbamate cyanoethyl ester (thiocyanate), whose polar molecular end is a dithiocarbamate group, which is effective for collecting Zn on the surface of zinc sphalerite after copper sulfate activation. 2+ It exhibits strong chelating ability and significantly superior collecting power compared to xanthate-based reagents. The introduction of polar cyano groups into the molecular side chains allows for the binding of more water molecules to form a stable hydration layer, enhancing the dispersibility and anti-precipitation ability of the reagent in low-temperature slurries from a molecular structure perspective. The entire molecule has an aliphatic structure, free of benzene rings, aromatic groups, and other recalcitrant groups. The functional adjuvant selected is 2-octanol, a short-chain fatty alcohol molecule with a small molecular size, which can insert into the palisade layer of the collector micelles, reducing the interfacial energy of micelle formation. It also has solubilizing and foam-stabilizing effects, further improving the solubility and dispersibility of the reagent at low temperatures. The functional adjuvant selected is a non-polar hydrocarbon oil, which fills the hydrophobic gaps in the micelles, enhancing the overall collecting power while lowering the system's freezing point and improving the low-temperature fluidity of the oily reagent.
[0012] (3) Environmentally friendly molecular structure design All composite collectors adopt aliphatic molecular structures and do not introduce aromatic groups such as aniline, phenyl, and naphthyl groups throughout the process. This avoids the inherent defects of the difficulty in biodegradation of aromatic compounds at the molecular level, achieving a biodegradation rate of ≥75% in 48 hours. The COD load of mineral processing wastewater is reduced by more than 60% compared with the traditional aniline black powder and ethyl thiocyanate system.
[0013] 2. Principle of Directional Control of Interfacial Chemical Parameters Based on molecular design, the three core interface parameters of hydrophilic-lipophilic balance (HLB), critical micelle concentration (CMC), and cloud point are precisely controlled through quantitative formulation and special preparation process. This results in a composite collector that matches the interface requirements of lead-zinc sulfide ore flotation, rather than being a natural result of simple compounding.
[0014] (1) Regulation of hydrophilic-lipophilic balance (HLB) The control objective is to precisely match the hydrophilicity / hydrophobicity of the reagent system with the surface characteristics of the target mineral, ensuring both sufficient dispersion in the aqueous phase and the formation of a stable hydrophobic adsorption layer on the mineral surface. The control principle involves calculating the HLB value of a single component using the Davis group contribution method, with the HLB of the compound system being the mass-weighted average of all components. By adjusting the proportions of components with different HLB values, the system's HLB is locked within the target range. Regarding formulation ratio control, HX-01 uses a ratio of 60-80 parts butylammonium black reagent, 15-30 parts sulfur-nitrogen ester, and 3-12 parts non-polar oil to precisely control the system's HLB between 7.5 and 9.0. This range is the optimal range for selective adsorption of galena: below 7.5, the oleophilicity is too strong, leading to easy agglomeration and poor dispersibility in the slurry; above 9.0, the hydrophilicity is too strong, resulting in insufficient hydrophobic adsorption on the mineral surface and decreased collecting power. HX-02 precisely controls the HLB of the system within a ratio range of 65-90 parts of thiocyanate, 2-8 parts of 2-octanol, and 4-15 parts of non-polar oil, maintaining it between 8.0 and 9.5. The zinc flotation reagents need to be adapted to the enhanced hydrophilicity of the sphalerite surface after activation; therefore, the ratio is slightly higher than that of HX-01 to ensure better water dispersibility and low-temperature stability. In terms of process, the isothermal stirring and maturation step ensures thorough mixing of all components, avoiding uneven HLB distribution caused by localized component segregation and guaranteeing overall uniform and stable HLB across the system.
[0015] (2) Critical micelle concentration (CMC) regulation The control objective is to minimize the system's CMC by reducing ineffective micelle aggregation of the reagent in the aqueous phase, enabling saturated adsorption on the mineral surface at lower reagent concentrations and reducing reagent consumption per unit. The control principle is that a single surfactant has a high CMC. By combining two or more structurally matched surfactants, the hydrophobic association between molecules forms tightly packed mixed micelles, significantly reducing the micelle formation free energy and thus substantially lowering the system's CMC. The addition of non-polar auxiliaries further fills the micelle core, enhancing this effect. Regarding synergistic formulation, the combination of butylammonium black reagent and thiocyanate in HX-01, with their matching polar head group sizes and complementary hydrophobic carbon chain lengths, forms tightly packed mixed micelles, reducing the CMC by more than 30% compared to a single component. The addition of non-polar hydrocarbon oil to fill the micelle core further reduces the interfacial tension, further lowering the CMC by approximately 15%, ultimately achieving a CMC ≤ 32 mg / L. In HX-02, thiocyanate and 2-octanol are combined. The small molecules of 2-octanol insert into the micelle palisade layer, reducing micelle curvature and formation energy. Combined with the core-filling effect of non-polar oil, the final CMC is ≤28mg / L. Regarding process curing control, constant temperature stirring and curing at 20~60℃ for 1.5~2h allows for full association of molecules of each component, forming a uniform and stable mixed micelle, eliminating CMC fluctuations caused by localized concentration unevenness. The low-temperature oil addition process below 30℃ avoids the non-polar oil from damaging the already formed micelle structure at high temperatures, ensuring that hydrocarbon oil is uniformly filled in the micelle core, achieving a stable reduction in CMC. If oil is added at high temperatures, the hydrocarbon oil will damage the micelle hydration layer, leading to micelle disintegration and a CMC increase of more than 30%.
[0016] (3) Targeted enhancement and regulation of cloud point The control objective is to raise the cloud point temperature of the reagent system, ensuring that the reagent does not separate or precipitate in the low-temperature slurry during winter in high-altitude mining areas, and that the separation indicators remain stable. The control principle is that the cloud point is essentially the critical temperature at which temperature changes cause the surfactant hydration film to rupture and micelles to aggregate; the more stable the micelle structure and the thicker the surface hydration layer, the higher the cloud point. Through molecular structure design, compound control, and process assurance, the cloud point of the system can be significantly improved. Inherent advantages of molecular structure: The cyano group in the thiocyanate molecule is a strongly polar group, which can bind more water molecules, thicken the hydration film on the micelle surface, and improve the temperature stability of the micelles—a structural characteristic not possessed by traditional xanthates and black powder molecules. Compound control of formulation: 2-octanol, as a short-chain alcohol, is inserted into the micelle palisade layer, increasing the hydrophilic sites at the micelle interface and simultaneously adjusting the micelle curvature to reduce the tendency for hydrophobic aggregation between micelles; non-polar oil uniformly fills the micelle core, preventing micelle aggregation due to hydrophobic interactions. Process assurance: The low-temperature oiling process adds hydrocarbon oil below 30℃ to avoid the hydrocarbon oil damaging the hydration layer on the micelle surface at high temperatures; the constant-temperature curing process makes the micelle particle size uniform (average particle size ≤5μm) to avoid premature aggregation of large-particle micelles, ultimately achieving a cloud point of ≥14℃ for HX-01 and ≥15℃ for HX-02, which is 4~5℃ higher than that of a simple physical compound system.
[0017] Secondly, the present invention protects the preparation method of the above-mentioned composite collector, including the preparation process of copper-lead mixed flotation collector HX-01 and the preparation process of zinc flotation collector HX-02. The preparation process of the copper-lead mixed flotation composite collector HX-01 is as follows: esterification reaction, neutralization reaction, sulfur-nitrogen ester synthesis, constant temperature compounding and maturation, and low temperature oil addition and shaping. The preparation process of the zinc flotation composite collector HX-02 is as follows: one-step synthesis of sulfur-nitrogen ester by segmented temperature control, constant temperature compounding and maturation, and low temperature oil addition and shaping.
[0018] Furthermore, the sulfur-nitrogen ester cooling synthesis reactor is equipped with a disc-type condenser, the cooling circulating medium is frozen brine, and the maximum reaction temperature inside the cooling synthesis reactor does not exceed 65°C.
[0019] Furthermore, throughout the entire preparation process of the composite collector, all raw materials, intermediate materials between processes, and the final product are transported through a vacuum negative pressure conveying system with a vacuum degree of -0.01 to -0.05 MPa, which can effectively prevent the escape of volatile agents and improve production safety and product stability.
[0020] Thirdly, this invention also protects the application of the above-mentioned composite collector in the flotation of lead-zinc sulfide ores. The flotation process consists of a single closed-circuit ball milling classification, a mixed flotation of copper and lead (roughing, scavenging, and cleaning), and a flotation of lead tailings (roughing, scavenging, and cleaning) for zinc. No lime is added throughout the process, and zinc sulfate is used only as a zinc mineral inhibitor.
[0021] Furthermore, the applicable raw ore is high-sulfur lead-zinc sulfide ore, with pyrrhotite accounting for more than 30% of the total iron sulfide minerals; the closed-circuit flotation process can achieve lead and zinc recovery rates exceeding 90%, with zinc concentrate iron content ≤11%, and significantly improved recovery rate of associated silver.
[0022] Fourthly, the present invention also protects an intelligent multi-stage emulsification dosing system adapted to the above-mentioned composite collector. The system consists of a three-layer closed-loop architecture from top to bottom, namely, a field sensing layer 10, a local control layer 11, and an execution device layer. Data and control commands are transmitted through electrical signal links. The execution device layer transports the reagent and process water through fluid pipelines. It is specially designed for the characteristics of oily collectors in lead-zinc sulfide ores, which have high viscosity and are prone to precipitation at low temperatures.
[0023] The on-site sensing layer collects the operating parameters of the slurry and reagents, the local control layer calculates and outputs control commands based on the parameters, and the execution equipment layer completes the constant temperature delivery, two-stage emulsification and jet dosing of the reagents, realizing closed-loop dynamic adjustment of the dosage and efficient dispersion of the reagents.
[0024] The field sensing layer 10 is the data acquisition input terminal of the system, consisting of seven independent parallel sensors. Each sensor is deployed at a corresponding monitoring point, independently acquiring parameters and transmitting electrical signals to the local control layer 11. These sensors include a pH probe 101, a slurry concentration meter 102, a slurry flow meter 103, a reagent temperature sensor 104, a liquid level sensor 105, a pressure sensor 106, and a leakage sensor 107, which are used to monitor slurry pH, slurry concentration, slurry flow rate, reagent temperature, reagent tank level, pipeline pressure, and leakage status, respectively, providing basic data for closed-loop control. The local control layer 11 serves as the system's computation and decision-making center, coordinating data reception and control command issuance. It includes a main control module 111, a PID calculation module 112, a pump drive module 113, a data storage module 114, a communication module 115, and a human-machine interaction module 116. The main control module 111 coordinates data reception, model invocation, and command issuance. The PID calculation module 112 incorporates a slurry parameter-reagent dosage matching model for the composite collector, outputting a dosage adjustment signal. The pump drive module 113 converts the calculation signal into a frequency converter output to the execution equipment layer, controlling the speed of each pump. The data storage module 114 records operating data and reagent consumption. The communication module 115 supports access to the concentrator's DCS central control system. The human-machine interaction module 116 is used for parameter setting and status display. The execution equipment layer is the functional execution end of the system. Along the drug flow direction, the drug storage tank 2, metering pump 4, filter device 5, primary pre-emulsification pump 6, secondary high-shear emulsification pump 7, and Venturi jet disperser 8 are sequentially connected on the drug fluid pipeline. The outlet of the Venturi jet disperser 8 is connected to the flotation cell 12. The top inlet of the drug storage tank 2 is connected to the vacuum feeding unit 1 pipeline. The outer wall of the drug storage tank 2 and the outer side of the front section of the main drug delivery pipeline are wrapped with a constant temperature heating module 3 to maintain stable drug temperature. The process water pipeline 13 is connected to the inlet of the primary pre-emulsification pump 6 to provide dilution water. The system also has a safety protection module 9, whose interlock control terminal is electrically connected to the metering pump 4, primary pre-emulsification pump 6, and secondary high-shear emulsification pump 7 respectively, to achieve fault interlock protection.
[0025] Furthermore, the primary pre-emulsification pump, the secondary high-shear emulsification pump, and the metering pump are all explosion-proof pump bodies; the average particle size of the microemulsion formed after two-stage emulsification is ≤5μm; and the comprehensive utilization rate of the agent is increased by more than 15% compared with the traditional direct dosing method.
[0026] Compared with existing technologies, the present invention has the following beneficial effects: 1. The synergistic design of two-stage special composite collectors enables efficient separation of lead and zinc in high-sulfur ores without the need for lime, breaking the technical prejudice that high-sulfur ores must be separated by high alkali. The recovery rates of lead and zinc both exceed 90%, the iron content of zinc concentrate is reduced to below 11%, and the recovery rate of associated silver is more than 10 percentage points higher than that of traditional high-alkali processes.
[0027] 2. Through the synergistic effect of molecular design, quantitative compounding, and process solidification, precise control of HLB, CMC, and cloud point is achieved. When the slurry temperature is as low as 10℃, the metal recovery rate fluctuation is controlled within 1.5 percentage points, which solves the industry pain point of large production fluctuations in high-altitude and cold mining areas during winter. The effect is far superior to the existing simple compounding technology.
[0028] 3. The low-temperature oil addition process works synergistically with the formulation to stabilize the micelle structure. The finished product can be stored at room temperature and sealed for 12 months without stratification, which is far superior to the 3-month storage period of traditional compound drugs.
[0029] 4. The dedicated intelligent dosing system is highly matched with the physicochemical properties of the reagents. The constant temperature delivery ensures the accuracy of low-temperature metering. Two-stage emulsification and jet dispersion greatly improve the dispersibility. Closed-loop control adapts to mineral fluctuations, and the overall reagent consumption is reduced by more than 15%.
[0030] 5. The all-aliphatic molecular structure enables the agent to achieve a biodegradation rate of ≥75% within 48 hours, reducing the COD load of wastewater by more than 60%; after eliminating the addition of lime, the cost of pipe scaling repair is reduced by 70%, and the overall mineral processing cost is reduced by more than 12%. Attached Figure Description
[0031] Figure 1Optical slides (partial slides) used for rock and mineral identification of raw ore. Figure 2 Thin sections (partial thin sections) for identification of original ore rocks and minerals. Figure 3 The grinding fineness test process flow; Figure 4 The grinding process steps are as follows; Figure 5 Experimental process flow for the types of collectors used in copper-lead mixed flotation; Figure 6 Experimental procedure for dosage of copper-lead mixed-selection collector; Figure 7 Procedure for selecting the dosage of zinc collector; Figure 8 Procedure for selecting the dosage of zinc sulfate; Figure 9 For closed-circuit process testing of flotation of lead-zinc sulfide ore; Figure 10 This is a schematic diagram of the intelligent multi-stage emulsification dosing system of the present invention.
[0032] In the diagram, 1. Vacuum feeding unit; 2. Chemical storage tank; 3. Constant temperature heating module; 4. Metering pump; 5. Filtration device; 6. Primary pre-emulsification pump; 7. Secondary high-shear emulsification pump; 8. Venturi jet disperser; 9. Safety protection module; 10. Field sensing layer; 101. pH probe; 102. Slurry concentration meter; 103. Slurry flow meter; 104. Reagent temperature sensor; 105. Liquid level sensor; 106. Pressure sensor; 107. Leakage sensor; 11. Local control layer; 111. Main control module; 112. PID calculation module; 113. Pump drive module; 114. Data storage module; 115. Communication module; 116. Human-machine interaction module; 12. Flotation cell; 13. Process water pipeline. Detailed Implementation
[0033] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. In addition, unless otherwise specified, the raw materials used in the embodiments and comparative examples of the present invention are all conventional commercially available industrial-grade products in the art.
[0034] Example 1
[0035] A method for preparing a composite collector for flotation of lead-zinc sulfide ore In this embodiment, a composite collector with a preferred ratio is prepared. Throughout the preparation process, raw materials, intermediate materials, and finished reagents are transported in a closed system using a vacuum negative pressure conveying system. The system vacuum degree is controlled at -0.02 MPa. The specific steps are as follows: 1. Preparation of copper-lead mixed flotation collector HX-01 (1) Esterification reaction: n-Butanol is added to a reaction vessel with a cooling jacket, and phosphorus pentasulfide is added at a mass ratio of n-Butanol to phosphorus pentasulfide of 4:1. The esterification reaction is carried out under stirring and controlled at 75°C. The heat of reaction is removed by circulating cooling water to generate crude dibutyl dithiophosphate. (2) Neutralization reaction: Liquid ammonia was continuously introduced into the crude product for neutralization to obtain butylammonium black powder; (3) Synthesis of sulfur nitrogen ester: acrylonitrile and carbon disulfide were added to the synthesis vessel, the cooling system was turned on, and diethylamine was added dropwise at a rate of 6 L / h under controlled temperature of 40℃. The molar ratio of raw materials was diethylamine:acrylonitrile:carbon disulfide = 0.8:1:1.2. After the addition was completed, the reaction was kept at the temperature until the endpoint was reached to obtain diethylamino dithiocarbamate alkyl ester. (4) Constant temperature compounding and maturation: Take 72 parts by weight of butylammonium black medicine and 22 parts by weight of sulfur nitrogen ester, and transport them to the temperature-controlled compounding kettle through vacuum negative pressure. Stir and mix for 1.8 h at 40℃ and 250 r / min, and then let it stand at a constant temperature for 11 h to form a stable molecular association mixed micelle system. (5) Low temperature oil addition and shaping: Cool the material in the kettle to 28°C, add 6 parts of kerosene, stir and mix thoroughly, filter after quality inspection, and then seal and fill.
[0036] 2. Preparation of zinc flotation collector HX-02 (1) Segmented temperature-controlled one-step synthesis of thiocyanate: to 3m 3 Acrylonitrile and carbon disulfide were added to a jacketed cooling synthesis reactor with a disc-type condenser. The cooling circulating medium was frozen brine. The reactor was pre-cooled to 30°C by the frozen brine, and diethylamine was added dropwise at a rate of 6 L / h. The temperature of the first 2 / 3 of the material was controlled at 30°C, and the temperature of the remaining material was raised to 50°C. After the addition was completed, the temperature was maintained at 50°C for 1.5 h. The total reaction time was 6.2 h, and a brownish-black oily thiocyanate with a purity of 82% was obtained. (2) Constant temperature compounding and maturation: Take 80 parts by weight of thiocyanate and 5 parts by weight of octanol, and put them into the compounding kettle through vacuum negative pressure conveying. Stir at 40℃ for 1.8h to form a uniform mixed micelle system. (3) Constant temperature compounding and maturation: Cool the material in the kettle to 28°C, add 10 parts of 0# diesel oil and mix well. After inspection and approval, seal and fill.
[0037] The HX-01 sample in this embodiment had an HLB of 8.2, a CMC of 30 mg / L, a cloud point of 14.5°C, a 48-hour biodegradation rate of 78.2%, and an average micelle size of 4.2 μm. The HX-02 sample had an HLB of 8.7, a CMC of 26 mg / L, a cloud point of 15.5°C, a 48-hour biodegradation rate of 76.5%, and an average micelle size of 3.8 μm.
[0038] Example 2
[0039] Application of a composite collector for flotation of lead-zinc sulfide ores The composite collector prepared in Example 1 was used to conduct a closed-circuit flotation test on a high-altitude, high-sulfur lead-zinc sulfide ore. The chemical multi-element analysis of the raw ore is shown in Table 1. 100% of the lead in the ore was hosted in galena, 100% of the zinc was hosted in sphalerite, and pyrrhotite accounted for 32% of the total iron sulfide minerals. Associated with Au 1.90 g / t and Ag 19.89 g / t.
[0040] Table 1. Results of multi-element chemical analysis of the raw ore (%, gold and silver are in g / t).
[0041] 1. Grinding fineness test Based on preliminary exploratory experiments, the reagent formulation was determined, and grinding fineness condition tests were conducted. The process flow is attached. Figure 3 As shown in Table 2, the experimental results are as follows.
[0042] Table 2 Results of grinding fineness test
[0043] As shown in Table 2, the grinding fineness is better when it is 61.70% to 74.20% of -0.074 mm. Based on the actual production conditions on site, the grinding fineness is determined to be 67.00% of -0.074 mm.
[0044] The specific grinding and classification process is as follows: the raw ore is crushed to a particle size of -12mm and fed into the powder bin, then conveyed by belt to a first-stage ball mill. The ball mill discharge is then pumped by a ceramic pump to a hydrocyclone for classification. The overflow fineness of the hydrocyclone is -0.074mm (67%), and the pulp concentration is 41%, which is then sent to the flotation process. The hydrocyclone underflow is returned to the ball mill to form a closed-circuit grinding system (see appendix for details). Figure 4 ).
[0045] 2. Test on mixed copper-lead flotation conditions Under the condition that the grinding fineness of -0.074 mm accounts for 67.00%, experiments were conducted on the types and dosages of collectors for copper-lead mixed flotation. The experimental procedure for collector types is attached. Figure 5 The experimental results are shown in Table 3.
[0046] Table 3. Test Results of Copper-Lead Mixed Collector Types
[0047] As shown in Table 3 above, HX-01 has the highest cumulative lead recovery rate in coarse scavenging and the least entrainment of zinc minerals when used as a copper-lead co-flotation collector, exhibiting the best selectivity. Therefore, HX-01 was selected as the copper-lead co-flotation collector.
[0048] A dosage test of HX-01 collector was conducted. The test procedure is attached. Figure 6 The experimental results are shown in Table 4.
[0049] Table 4 Results of the test on the dosage of copper-lead mixed separator collector
[0050] As shown in Table 4, the comprehensive index of copper and lead recovery rate is optimal when the dosage of collector HX-01 is 40g / t. Further increasing the dosage significantly increases the rough concentrate yield, but the recovery rate improvement is limited. Therefore, the dosage of copper-lead mixed flotation rougher collector HX-01 is selected as 40g / t.
[0051] The specific process involves adding 300 g / t of zinc sulfate as a sphalerite inhibitor after the grinding overflow slurry is conditioned. During the roughing operation, 40 g / t of HX-01 collector is added. During the three scavenging operations, 15 g / t, 8 g / t, and 5 g / t of HX-01 are added in stages. During the three cleaning processes, 80 g / t, 40 g / t, and 20 g / t of zinc sulfate are added in sequence to further remove zinc and produce a copper-lead mixed concentrate. The slurry pH is maintained in the low-alkali range of 8.5 to 9.5.
[0052] 3. Zinc flotation conditions test Copper-lead flotation tailings are fed into zinc flotation operations to conduct tests on collector dosage and copper sulfate activator dosage. The test procedure for zinc flotation collector dosage is attached. Figure 7 The test results are shown in Table 5.
[0053] Table 5 Results of the zinc collector dosage test
[0054] As shown in Table 5, the zinc recovery rate is already at a relatively high level when the amount of collector HX-02 is 40 g / t. Further increasing the amount will have limited effect on improving the recovery rate. Therefore, the amount of zinc roughing collector HX-02 was selected to be 40 g / t.
[0055] A test was conducted on the dosage of copper sulfate activator. The test procedure is attached. Figure 8 The test results are shown in Table 6.
[0056] Table 6. Test results of zinc-copper sulfate dosage.
[0057] As shown in Table 6, the zinc recovery rate is close to its peak when the copper sulfate dosage is 300 g / t. Further increasing the dosage will result in very little improvement. Considering the overall cost, the copper sulfate dosage of 300 g / t was selected.
[0058] The specific process involves feeding copper-lead flotation tailings into zinc flotation slurry, adding 300 g / t of copper sulfate to activate iron sphalerite, adding 40 g / t of HX-02 collector for zinc roughing, and adding 12 g / t, 6 g / t, and 4 g / t of HX-02 in three separate scavenging operations; and adding 30 g / t, 15 g / t, and 8 g / t of zinc sulfate in three separate cleaning operations to gradually remove iron sulfide and gangue, thereby improving the grade of zinc concentrate.
[0059] 4. Closed-circuit process test for flotation of lead-zinc sulfide ore Based on the conditional tests, a closed-circuit flotation test was conducted on the entire process of "one roughing, three scavenging, and three refining." The test procedure is shown below. Figure 9 The results of the stable closed-circuit test are shown in Table 7.
[0060] (1) Grinding and classification: The raw ore is crushed to -12mm particle size and fed into the powder silo. It is then conveyed to the first-stage ball mill via belt. The ball mill discharge is pumped to the hydrocyclone for classification via ceramic pump. The overflow fineness of the hydrocyclone is -0.074mm, accounting for 67%, and the slurry concentration is 40~42%. It is then sent to the flotation process. The hydrocyclone sediment is returned to the ball mill to form a closed-circuit grinding process. (2) Copper-lead mixed flotation: After the grinding overflow is slurry adjusted, 300 g / t of zinc sulfate is added as a sphalerite inhibitor. 40 g / t of HX-01 collector is added during the roughing operation. 15 g / t, 8 g / t, and 5 g / t of HX-01 are added sequentially during the three scavenging operations. 80 g / t, 40 g / t, and 20 g / t of zinc sulfate are added sequentially during the three cleaning operations to further remove zinc and produce a copper-lead mixed concentrate. The pulp pH is maintained in the low-alkali range of 8.5 to 9.5. (3) Zinc flotation: The tailings from copper-lead flotation enter the zinc flotation slurry, and 300g / t of copper sulfate is added to activate iron sphalerite. 40g / t of HX-02 collector is added to the zinc roughing. 12g / t, 6g / t and 4g / t of HX-02 are added in three separate scavenging operations. 30g / t, 15g / t and 8g / t of zinc sulfate are added in three separate cleaning operations to gradually remove iron sulfide and gangue and improve the grade of zinc concentrate.
[0061] Table 7 Results of Closed-Circuit Flotation Tests for Lead-Zinc Sulfide Ores (%, Silver Grade in g / t)
[0062] As shown in Table 7, the stable indicators of the whole process closed-circuit test are: lead grade of lead concentrate 51.80%, total lead recovery rate 91.03%, and total silver recovery rate 41.70%; zinc grade of zinc concentrate 43.55%, total zinc recovery rate 90.94%, and iron content of zinc concentrate 10.82%, which are excellent.
[0063] Example 3
[0064] Intelligent multi-stage emulsification dosing system for composite collectors in the flotation of lead-zinc sulfide ores This system is compatible with lead-zinc sulfide ore beneficiation plants with a daily processing capacity of 2600t. It consists of three layers from top to bottom: a field sensing layer, a local control layer, and an execution equipment layer. Data and control commands are transmitted between layers via electrical signal links. Within the execution equipment layer, reagents and process water are transported via fluid pipelines (see attached diagram for details). Figure 10 The system's rated reagent dosing capacity is 0~200L / h, and the emulsification treatment capacity is 1~5m³. 3 / h.
[0065] 1. Core working principle of the system (1) Multi-stage emulsification and dispersion principle: A graded refinement mechanism of two-stage emulsification and jet dispersion is adopted. The first stage of pre-emulsification completes the initial crushing of the oil phase, forming a coarse emulsion of 50~100μm; the second stage of high shearing refines the oil droplets into stable microemulsions with a particle size ≤5μm through high-frequency shearing of stator and rotor, greatly increasing the specific surface area of the reagent; finally, the microemulsion is directly injected into the mainstream field of the slurry through the Venturi jet disperser, and dispersed again with the help of jet turbulence, avoiding microemulsion agglomeration, so that the reagent can contact the mineral particles instantly and uniformly, significantly improving the effective utilization rate and reducing unit consumption.
[0066] (2) Intelligent closed-loop control principle: The core logic is to determine the dosage based on the dry ore quantity. The dry ore processing volume is calculated in real time by measuring the slurry flow rate and concentration, and the baseline dosage is output by calling the preset reagent consumption model. A reagent temperature correction coefficient is introduced to offset the influence of temperature on reagent viscosity and metering accuracy. The system automatically corrects the pump speed through a PID algorithm to achieve adaptive following of the dosage as the ore quality fluctuates, eliminating the lag and error of manual dosing and ensuring the stability of the sorting indicators.
[0067] 1. System operation process (1) System startup and automatic replenishment: After the system is powered on and initialized, the liquid level sensor 105 detects the liquid level of the storage tank 2. If it is lower than the set lower limit, the main control module 111 sends a replenishment signal and the vacuum feeding unit 1 starts. The barrel-packaged HX-01 and HX-02 collectors are sucked into the corresponding storage tanks by negative pressure. When the liquid level reaches the set upper limit, the vacuum feeding unit 1 automatically stops.
[0068] (2) Constant temperature preheating preparation: The constant temperature heating module 3 starts synchronously and automatically adjusts the heating power according to the feedback data of the drug temperature sensor 104 to stabilize the drug temperature in the drug storage tank 2 and the delivery pipeline at 25℃, eliminating the influence of low ambient temperature on drug flowability and metering accuracy, and preparing for subsequent emulsification and dosing.
[0069] (3) Metering and pre-treatment of filtration: The local control layer 11 receives the slurry flow rate and concentration signals from the field sensing layer 10, and calculates the target dosage corresponding to the current dry ore quantity through the PID calculation module 112. The pump drive module 113 outputs the frequency conversion signal to the metering pump 4. The metering pump 4 draws the agent from the storage tank 2 according to the set flow rate, removes impurities through the 100-mesh filter, and then delivers it to the inlet of the primary pre-emulsification pump 6.
[0070] (4) Two-stage emulsification and refinement: The reagent and process water are combined at the inlet of the first-stage pre-emulsification pump 6. After the initial stirring and mixing by the first-stage pre-emulsification pump 6, a coarse emulsion with a particle size of about 80 μm is formed. The coarse emulsion then enters the second-stage high-shear emulsification pump 7, where it is repeatedly torn and dispersed under the high-speed shearing action of the stator and rotor, and finally forms a uniform and stable microemulsion with a particle size of ≤5 μm, thus completing the refinement and dispersion of the reagent.
[0071] (5) Jet addition and dispersion: The prepared microemulsion is transported to the Venturi jet disperser 8 corresponding to the flotation operation; the high-speed process water flow generates negative pressure through the Venturi tube, which draws in the microemulsion and impacts and disperses it again, and directly injects it into the mainstream of the slurry in the flotation cell 12, so that the reagent droplets are instantly and uniformly dispersed in the slurry system and quickly adsorbed on the mineral surface.
[0072] (6) Real-time closed-loop dynamic adjustment: During operation, the field sensing layer continuously collects data such as slurry flow rate, concentration, pH, reagent temperature, pipeline pressure, and leakage status, and transmits them to the local control layer in real time; the main control module corrects the dosage in real time according to the mineral quality fluctuation: when the slurry concentration increases and the flow rate increases, the speed of the metering pump 4 is increased synchronously, and vice versa; at the same time, the volumetric efficiency of the metering pump is corrected according to the reagent temperature to ensure the dosing accuracy and realize the real-time matching of the dosage and the slurry status.
[0073] (7) Safety interlock protection: The safety protection module 9 monitors the equipment status in real time during operation. When a fault occurs such as low liquid level in the storage tank 2, leakage in the pipeline, overload of the pump, or abnormal pipeline pressure, an audible and visual alarm is immediately triggered, and corresponding interlock actions are performed according to the fault level: a warning prompt for minor faults, and direct interlock shutdown for serious faults to avoid equipment damage and drug leakage, and to ensure the safe and stable operation of the system.
[0074] According to on-site industrial testing, after the addition of this dosing system, the overall consumption of the collector was reduced by 17.8% compared with the traditional manual direct dosing, the utilization rate of the agent was increased by 19.2%, the daily fluctuation range of the sorting index was reduced by more than 60%, and the system operated stably in low-temperature winter environments without pipeline blockage or metering inaccuracy.
[0075] Comparative Example To verify the technical effect of the present invention, four sets of comparative examples were set up for parallel comparison with the embodiments of the present invention. All test mineral samples, equipment parameters and operating procedures were kept consistent to eliminate interference from irrelevant variables.
[0076] Comparative Example 1, closest to the prior art: The zinc collector was prepared according to Example 1 of CN115672561B, and the copper-lead flotation section used a combination of industrial conventional ethyl thiocyanate and butanium black powder in a mass ratio of 1:1.
[0077] Comparative Example 2, Traditional Industrial Reagent System: 25# black powder was used for the copper-lead segment, butyl xanthate was used for the zinc segment, and a high-alkali lime process was used to adjust the slurry pH to 11.5.
[0078] Comparative Example 3, omitting the low-temperature oil addition process: using the raw material ratio of Example 1 of the present invention, after compounding and maturation, without cooling, non-polar hydrocarbon oil is directly added at 40°C and mixed evenly, and the remaining preparation steps are exactly the same.
[0079] Comparative Example 4, reagents adapted for high-alkali process: The HX-01 and HX-02 reagents of the present invention were used, but lime was added during the flotation process to adjust the pH of the pulp to 11.5, and the other flotation conditions were the same as in Example 2.
[0080] Table 8 Comparison of core physicochemical parameters of each group of drugs
[0081] As shown in Table 8, the composite collector of the present invention achieves precise control of HLB, lower critical micelle concentration, and higher turbidity point. Its biodegradability and long-term storage stability are significantly better than those of existing conventional agents. The parameters deteriorate significantly after omitting the low-temperature oiling process, which confirms that this process is the core link to ensure the interfacial performance of the agent.
[0082] Table 9 Comparison of indices for closed-loop flotation at room temperature (25℃)
[0083] As shown in Table 9, under low-alkali and lime-free conditions, the recovery rates of lead and zinc in the system of this invention both exceeded 90%, and the recovery rate of associated silver was increased by more than 11 percentage points compared with the traditional high-alkali process, while the iron content of zinc concentrate was lower. When the reagent was forcibly adapted to the high-alkali process, the zinc recovery rate decreased significantly, which proved the synergistic compatibility between the reagent and the low-alkali process.
[0084] Table 10 Comparison of indicators for the entire closed-loop flotation process at low temperature (10℃)
[0085] As shown in Table 10, at a low temperature of 10℃, the lead and zinc recovery rates of the reagent of this invention fluctuated by less than 1.5 percentage points, and the low temperature stability was far superior to that of the prior art. After omitting the low temperature oiling process, the recovery rate fluctuation range increased by more than 3 times, which fully demonstrates the adaptability value of interface parameter control and special preparation process to high-altitude and cold mineral processing scenarios.
[0086] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A composite collector for flotation of lead-zinc sulfide ore, characterized in that, The composite collector is composed of copper-lead mixed flotation collector HX-01 and zinc flotation collector HX-02; the composite collector does not contain benzene ring structures and has a biodegradability rate of ≥75% after 48 hours. The copper-lead mixed flotation collector HX-01 comprises the following components by weight: 60-80 parts of dialkyl dithiophosphate, 15-30 parts of thionitrogen ester, and 3-12 parts of nonpolar hydrocarbon oil; the collector HX-01 has a hydrophilic-lipophilic balance value (HLB) of 7.5-9.0, a critical micelle concentration (CMC) ≤ 32 mg / L, and a cloud point ≥ 14℃; The zinc flotation collector HX-02 comprises the following components by weight: 65-90 parts of thiocyanate, 2-8 parts of hydroxy fatty alcohol, and 4-15 parts of non-polar hydrocarbon oil; the zinc flotation collector HX-02 has a hydrophilic-lipophilic balance value (HLB) of 8.0-9.5, a critical micelle concentration (CMC) ≤ 28 mg / L, and a cloud point ≥ 15℃.
2. The composite collector according to claim 1, characterized in that, In the copper-lead mixed flotation collector HX-01, the dialkyl dithiophosphate is butylammonium black powder, and the thiocyanate is diethylaminodithiocarbamate alkyl ester; in the zinc flotation collector HX-02, the thiocyanate is N,N-diethyldithiocarbamate cyanoethyl ester, and the hydroxy fatty alcohol is 2-octanol.
3. The method for preparing a composite collector for flotation of lead-zinc sulfide ore according to claim 2, characterized in that, This includes the preparation process of copper-lead mixed flotation collector HX-01 and the preparation process of zinc flotation collector HX-02; The preparation process of the copper-lead mixed flotation collector HX-01 specifically includes the following steps: Step S1, Esterification reaction: n-Butanol is added to a reactor with a cooling jacket, and phosphorus pentasulfide is added at a mass ratio of n-butanol to phosphorus pentasulfide of 4:
1. The esterification reaction is carried out under stirring and controlled at 70~80℃. The heat of reaction is removed by circulating cooling water to generate crude dibutyl dithiophosphate. Step S2, neutralization reaction: Liquid ammonia is continuously introduced into crude dibutyldithiophosphate for neutralization to obtain butylammonium black powder; Step S3, Synthesis of sulfur-nitrogen esters: Acrylonitrile and carbon disulfide are added to the synthesis reactor, the cooling system is turned on, and diethylamine is added dropwise at a rate of 5-8 L / h while maintaining the temperature at 20-60℃. After the addition is completed, the temperature is maintained until the reaction is complete to obtain diethylamino dithiocarbamate alkyl ester; the molar ratio of the raw materials is diethylamine:acrylonitrile:carbon disulfide = 0.8:1:1.
2. Step S4, constant temperature compounding and maturation: Butylammonium black powder and diethylaminodithiocarbamate alkyl ester are transported to a temperature-controlled compounding kettle, stirred and mixed at 20~60℃ and 200~300r / min for 1.5~2h, and then kept at a constant temperature for 10~12h to form a stable molecularly associated mixed micelle system. Step S5, Low-temperature oil addition and shaping: Cool the material in the compounding kettle to below 30°C, add non-polar hydrocarbon oil, stir and mix thoroughly, and then seal and fill after quality inspection and filtration. The preparation process of the zinc flotation collector HX-02 specifically includes the following steps: Step T1, one-step synthesis of thiocyanate in a segmented temperature-controlled manner: [The following text appears to be a separate, unrelated section:] ...to 3m 3 Acrylonitrile and carbon disulfide are added to a jacketed cooling synthesis reactor and pre-cooled to 20-40°C with chilled brine. Diethylamine is added at a dropping rate of 5-8 L / h. The temperature is controlled at 20-40°C during the first 2 / 3 of the material is added, and the temperature is raised to 40-60°C during the remaining material addition. After all the material is added, it is kept at 40-60°C for 1-2 hours. The total reaction time is 6-6.5 hours, and a brownish-black oily thiocyanate with a purity of ≥80% is obtained. Step T2, constant temperature compounding and maturation: Add thiocyanate and 2-octanol to the compounding kettle, stir at a constant temperature of 20~60℃ for 1.5~2h to form a homogeneous mixed micelle system; Step T3, Low-temperature oil addition and shaping: Cool the material in the reactor to below 30°C, add non-polar hydrocarbon oil and mix well. After inspection and approval, seal and fill.
4. The preparation method according to claim 3, characterized in that, In step T1, the sulfur-nitrogen ester cooling synthesis reactor is equipped with a disc-type condenser, the cooling circulating medium is frozen brine, and the maximum reaction temperature inside the cooling synthesis reactor does not exceed 65°C.
5. The preparation method according to claim 3, characterized in that, Throughout the entire preparation process of the composite collector, all raw materials, intermediate materials between processes, and finished products are transported through a vacuum negative pressure conveying system with a vacuum degree of -0.01 to -0.05 MPa.
6. The application of the composite collector according to claim 2, characterized in that, The composite collector is used for the flotation of sulfide lead-zinc ore. The flotation process consists of a single-stage closed-circuit ball milling and classification, a mixed flotation of copper and lead (roughing, scavenging, and cleaning), and a flotation of lead tailings (roughing, scavenging, and cleaning) and zinc (zinc flotation). The specific flotation process is as follows: Step S-1, Grinding and Classification: The raw ore is crushed to -12mm particle size and fed into the powder bin. It is then conveyed by belt to the first-stage ball mill. The ball mill discharge is pumped by a ceramic pump to the hydrocyclone for classification. The overflow fineness of the hydrocyclone is -0.074mm, accounting for 67%, and the pulp concentration is 40~42%, which is then sent to the flotation process. The underflow from the hydrocyclone is returned to the ball mill to form a closed-circuit grinding process. Step S-2, Copper-Lead Mixed Flotation: After conditioning the grinding overflow, add 300 g / t zinc sulfate as a sphalerite depressant. During the roughing operation, add 40 g / t of HX-01 collector. For the three scavenging operations, add 15 g / t, 8 g / t, and 5 g / t of HX-01 respectively. For the three cleaning operations, add 80 g / t, 40 g / t, and 20 g / t of zinc sulfate respectively for further zinc removal, producing a copper-lead mixed concentrate. The pulp pH is maintained in the low-alkaline range of 8.5–9.
5. Step S-3, Zinc Flotation: The tailings from the copper-lead flotation enter the zinc flotation slurry for conditioning. 300 g / t of copper sulfate is added to activate the iron sphalerite. For the zinc roughing, 40 g / t of HX-02 collector is added. During the three scavenging operations, 12 g / t, 6 g / t, and 4 g / t of HX-02 are added in stages. For the three cleaning operations, 30 g / t, 15 g / t, and 8 g / t of zinc sulfate are added in stages to gradually remove iron sulfide and gangue, thereby improving the grade of zinc concentrate.
7. The application according to claim 6, characterized in that, The chemical composition of the raw ore is as follows: Cu 0.28wt%, Pb 0.85wt%, Zn 2.80wt%, Fe 40.45wt%, S 19.52wt%, of which pyrrhotite accounts for more than 30% of the total iron sulfide minerals; lead is 100% hosted in galena, and zinc is 100% hosted in sphalerite, with associated Au 1.90g / t and Ag 19.89g / t; after closed-circuit flotation, the lead concentrate has a lead grade of 51.80wt%, a total lead recovery rate of 91.03%, and a silver recovery rate of 41.70%; the zinc concentrate has a zinc grade of 43.55wt%, a total zinc recovery rate of 90.94%; and the iron content of the zinc concentrate is ≤11%.
8. An intelligent multi-stage emulsification dosing system adapted to the composite collector of claim 1 or 2, characterized in that, The system consists of a field sensing layer, a local control layer, and an execution device layer, which transmit data and control commands through electrical signal links from top to bottom. The execution device layer transports chemicals and process water through fluid pipelines. The field sensing layer serves as the system's data acquisition input, consisting of seven independent and parallel sensors. Each sensor is deployed at a corresponding monitoring point, independently acquiring parameters and transmitting electrical signals to the local control layer. These sensors include a pH probe, slurry concentration meter, slurry flow meter, reagent temperature sensor, liquid level sensor, pressure sensor, and leakage sensor. These sensors are used to monitor slurry pH, slurry concentration, slurry flow rate, reagent temperature, reagent tank level, pipeline pressure, and leakage status, respectively, providing basic data for closed-loop control. The local control layer serves as the system's computation and decision-making center, coordinating data reception and control command issuance. It includes a main control module, a PID calculation module, a pump drive module, a data storage module, a communication module, and a human-machine interaction module. The main control module coordinates data reception, model invocation, and command issuance. The PID calculation module has a built-in slurry parameter-dosage matching model for the composite collector and outputs a dosing adjustment signal. The pump drive module converts the calculation signal into a frequency converter output to the execution equipment layer to control the speed of each pump. The data storage module records operational data and reagent consumption; the communication module supports connection to the DCS central control system of the ore dressing plant; the human-machine interaction module is used for parameter setting and status display. The execution equipment layer serves as the functional execution end of the system. Along the drug flow direction, a drug storage tank, metering pump, filter, primary pre-emulsification pump, secondary high-shear emulsification pump, and Venturi jet disperser are sequentially connected on the drug fluid pipeline. The outlet of the Venturi jet disperser is connected to the flotation cell. The top inlet of the drug storage tank is connected to the vacuum feeding unit pipeline. A constant temperature heating module is installed on the outer wall of the drug storage tank and the outer side of the front section of the main drug delivery pipeline to maintain stable drug temperature. The process water pipeline is connected to the inlet of the primary pre-emulsification pump to provide dilution water. The system also includes a safety protection module, whose interlock control terminals are electrically connected to the metering pump, primary pre-emulsification pump, and secondary high-shear emulsification pump respectively, achieving fault interlock protection.
9. The intelligent multi-stage emulsification dosing system according to claim 8, characterized in that, The primary pre-emulsification pump, the secondary high-shear emulsification pump, and the metering pump are all explosion-proof pump bodies; the average particle size of the microemulsion formed after two-stage emulsification is ≤5μm; the system is suitable for continuous and stable dosing in a sulfide lead-zinc ore beneficiation plant with a daily processing capacity of 2600t, and the comprehensive utilization rate of the reagents is increased by more than 15% compared with the traditional direct dosing.
Citation Information
Patent Citations
A zinc collector for lead-zinc ore, its preparation method and application
CN115672561B